2019
DOI: 10.1101/852707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zygotic pioneer factor activity of Odd-paired/Zic is necessary for establishing theDrosophilaSegmentation Network

Abstract: 31Because regulatory networks of transcription factors drive embryonic patterning, it is possible that 32 chromatin accessibility states impact how networks interact with information encoded in DNA. To 33 determine the interplay between chromatin states and regulatory network function, we performed 34 ATAC seq on Drosophila embryos over the period spanning the establishment of the segmentation 35 network, from zygotic genome activation to gastrulation. Chromatin accessibility states are 36 dynamic over this pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…These results suggest that Forkhead-like, D, Grh, and other factors such as Dref and Odd-paired (Opa) may have active roles in facilitating chromatin accessibility at gastrulation. Indeed, an important role for Opa in shaping chromatin accessibility during gastrulation was recently demonstrated ( Koromila et al, 2019 preprint; Soluri et al, 2019 preprint). This contrasts with regions that lost accessibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that Forkhead-like, D, Grh, and other factors such as Dref and Odd-paired (Opa) may have active roles in facilitating chromatin accessibility at gastrulation. Indeed, an important role for Opa in shaping chromatin accessibility during gastrulation was recently demonstrated ( Koromila et al, 2019 preprint; Soluri et al, 2019 preprint). This contrasts with regions that lost accessibility.…”
Section: Resultsmentioning
confidence: 99%
“…D binds to core promoters and enhancers in the embryo and is required for proper gene expression of thousands of genes ( Aleksic et al, 2013 ). Indeed, recent evidence has shown that Opa is required for hundreds of regions of accessible chromatin in the gastrulating embryo, demonstrating that individual factors can drive chromatin accessibility at this stage of development ( Koromila et al, 2019 preprint; Soluri et al, 2019 preprint). Opa, Grh and D are all factors that are broadly expressed at the transition to gastrulation and are required for proper gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…D is required for normal expression of some pair rule genes in Drosophila and for spider segmentation, and the expression of D orthologues in the segment addition zone is conserved throughout panarthropoda (Nambu & Nambu, 1996; Russell et al, 1996; Ma et al, 1998; Clark & Peel, 2018; Janssen et al, 2018; Paese et al, 2018; Baudouin-Gonzalez et al, 2020). In Drosophila, opa is required for late network activation and genome-wide regulatory changes (Clark & Akam, 2016; Koromila et al, 2019; Soluri et al, 2019). In other insects, opa is expressed in a band at the end of the segment addition zone, where a putative late network would be active, though Oncopeltus lack this pattern, implying this timer gene role may not be conserved across all insects (Green & Akam, 2013; Xiang et al, 2017; Janssen et al, 2011; Auman & Chipman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…60 One study found that CGIs primarily reside in the transcriptionally active regions and are unaffected by methylation through a variety of mechanisms like occupied TFs, RNA pol II, or H3K4me3, and nucleosome positioning is driven by DNMT blockage. 61 It becomes transcriptionally silenced if CGI becomes condensed in the promoter region. In contrast, via a sequence of enzymes, i.e., 10−11 translocases (TETs) known as TET1/2/3-governed-reactions, DNA that has been methylated can be changed back to its original cytosine base.…”
Section: Role Of Epigenetics In Skin Cancermentioning
confidence: 99%